Social Determinants and Reproductive Factors of the Menopausal Symptoms among Women in Tabriz-Iran - Mahasti Alizadeh; Manizheh Sayyah-Melli; Hanieh Ebrahimi; Maryamalsadat Kazemi Shishavan; Farzad Rahmani (Shahid Beheshti University of Medical Sciences, 2015)
Background: Menopause is a natural event in which different degrees of psychosomatic changes occur. The social, demographic and behavioral factors in different nations have a significant effect on symptoms of menopause. The aim of this study was to determine the relationship between the personal, demographic, social and reproductive factors with symptoms of menopause and the frequency of the mental and physical symptoms of menopause among women in Tabriz, Northwest of Iran.    Methods: A cross-sectional study was conducted in the clinics and health centers of Tabriz, East Azerbaijan and Iran. A total of 300 women aged 40-60 years filled a questionnaire on the socio demographic variables, reproductive history and symptoms checklist.   Results: Among the symptoms, muscle and joint pain (68.7%), and increased facial hair (20.5%) were the most and the least common ones respectively. According to participants, as age increases, the symptoms worsen (p=0.003).  The frequency of the symptoms of the employed women was less than those of retired ones and housewives (p=0.001). The physical and mental symptoms had negative relation with educational status (p<0.05). An increase in the number of the children, the history of the oral contraceptive use and dysmenorrhea had positive relation with the frequency of the symptoms.   Conclusion: The quality of life of the women during menopause worsens with an increase in age and number of children, whereas it improves with higher educational levels and employment.